Association between homocysteine and blood pressure in the NHANES 2003–2006: the mediating role of Vitamin C - Wu, Peng; Ma, Juan; Yang, Shaobin; Wu, Hailiang; Ma, Xueping; Chen, Dapeng; Jia, Shaobin; Yan, Ning (Frontiers in Nutrition, 2024)
The yearly escalation in hypertension prevalence signifies a noteworthy public health challenge. Adhering to a nutritious diet is crucial for enhancing the quality of life among individuals managing hypertension. However, the relationship between vitamin C and hypertension, as well as homocysteine, remains unclear. Objective: The primary aim of this investigation was to scrutinize the potential mediating role of Vitamin C in the association between homocysteine levels and blood pressure, utilizing data extracted from the National Health and Nutrition Examination Survey (NHANES) database. Methods: A total of 7327 participants from the NHANES 2003-2006 were enrolled in this crosssectional survey. The main information was obtained using homocysteine, Vitamin C, systolic blood pressure (SBP) and diastolic blood pressure (DBP). Correlation analysis was used to assess the correlation between homocysteine, SBP, DBP and vitamin C. Linear regression analysis was utilized to determine the β value (β) along with its 95% confidence intervals (CIs). Mediation analysis was performed to investigate whether the relationship between homocysteine and blood pressure was mediated by Vitamin C, and to quantify the extent to which Vitamin C contributed to this association.The results manifested that the homocysteine was positively associated with SBP (r=0.24, p <0.001) and DBP (r=0.03, p <0.05), while negatively correlated with Vitamin C (r=-0.008, p <0.001). Vitamin C was found to be negatively associated with SBP (r=-0.03, p <0.05) and DBP (r=0.11, p <0.001). Mediation effect analysis revealed that a partial mediation (indirect effect: 0.0247[0.0108-0.0455], P <0.001) role accounting for 11.5% of total effect, among homocysteine and SBP. However, the mediating effect of Vitamin C between homocysteine and DBP was not statistically significant. Conclusions: Hypertension patients should pay attention to homocysteine and Vitamin C level. What's more, hypertension patients ought to formulate interventions for Vitamin C supplementation as well as homocysteine reduce strategies to lower blood pressure.